HUBUNGAN PROFESI DAN PROFESIONAL HUKUM DALAM MENJAGA INTEGRITAS - Ahmad Alfayum; M. Agil Alamsyah (JURNAL ILMIAH NUSANTARA, 2025)
This research discusses the nature of the profession and professionalism in the context of the legal profession and the challenges it faces in Indonesia. The legal profession has a fundamental role in maintaining justice and public order, but it is often faced with various problems such as abuse of authority, ethical degradation, and the tendency to make the profession a mere business event. Through a normative legal research approach, this study highlights the values and principles that should be upheld by legal professionals, including integrity, competence, commitment, discipline, responsibility, and objectivity. This study also highlights the factors that cause the decline in the quality of legal professionalism in Indonesia, such as low integrity, collusion-based recruitment, a legal education system that does not pay attention to moral aspects, and weak enforcement of the professional code of ethics. A comprehensive reform of the education system and practice of the legal profession is needed in order to produce professionals who are not only competent in the field of law, but also have high ethics and social responsibility. Thus, the legal profession can again become an instrument of justice that works for the benefit of the wider community, not only as a means of seeking personal profit.